Physical activity through adolescence: Trajectories and predictors of change - Murphy, Kellie A (University of Ottawa (Canada), 2006)
Statement of the problem. Physical activity levels generally decrease during adolescence and adulthood. A better understanding of patterns and determinants of physical activity through adolescence can inform physical activity interventions aimed at youth. Methods of investigation. Subjects were 1206 Montreal adolescents followed over 4.5 years. Physical activity was measured using a modified Weekly Activity Checklist. Trajectories were identified using the multilevel model for change. Demographic, psychological, and behavioural predictors were explored separately by sex. Results. A cubic trajectory controlling for season emerged. Activity peaked at age 13.5, decreased, and increased again at age 16.5, but showed significant heterogeneity both within- and between-subjects. Males had higher physical activity levels than females at all ages. Depression, stress, sedentary behaviours, and alcohol use affected physical activity trajectories. Conclusion. Physical activity levels follow a complex, curvilinear pattern during adolescence, and begin to decrease by age 14. Physical activity promotion interventions should focus toward this age group to promote increased physical activity participation.
Keywords: Health Sciences, Public Health.; Health Sciences, Recreation.